Climate change and sustainable development – the ethical dimension - Dzwonkowska, Dominika (Studia Ecologiae et Bioethicae, 2013)
Tourism is one of the fastest developing sectors of the economy and one of the sectors extremely vulnerable to climate change. As all tourism destinations rely on their unique natural or cultural values, any changes in climate and an increase in extreme climate events impact on the industry more than the other economic sectors. The article presents the relationship between climate change and tourism, focusing on the ethical dimension of sustainable tourism. The aim of the article is to present the moral questions on sustainability in tourism in the context of climate change. It focuses on environmental values and presents its role in the context of sustainable tourism development.